EFEKTIVITAS MODEL PEMBELAJARAN RECIPROCAL TEACHING DALAM PENINGKATAN KEMANDIRIAN DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI (Studi Eksperimen Pada Siswa Kelas XI IPA SMA Negeri 6 Padang) - Sri Annisa Agusti; Elvi Rahmi; Rita Syofyan (Jurnal Ecogen, 2018)
Reciprocal Teaching is learning model that consisting of four strategies are summarizing, questioning generating, clarifying and predicting. The using of  reciprocal teaching  expected to increase independence and learning achievement students on economic subjects. This study aims to see the effectiveness of  reciprocal teaching  for increase the independence and learning achievement  students on economic subjects. This study is the research of quasi experiment. The population in this study are all students of XI IPA class SMA Negeri 6 Padang. The methods in this research is  descriptive analysis and inferensial analysis t test using the SPSS program version 21. The result of this research are 1) There are no difference independence students by using  reciprocal teaching with the independence of students by using the conventional models. 2) There are difference learning achievement  students by using reciprocal teaching with learning achievement  students by using the conventional models. The using of learning models of reciprocal teaching isn’t quite effective in an increase in the independence of students learning. The value of effect size obtained againts the independence of learning 0,23 that included in the low criteria. If viewed the percentage based on the curves normal 0 to Z can be obtained a number of 0,0948, that is the contribution of learning models of reciprocal teaching in an increase in the independence of learning students which amounted to 9,48%. But the using of learning models of reciprocal teaching is effective in an increase learning achievement  students, it looks based on the accounts effect size then found the number of 0,71 with high criteria. If viewed the percentage based on the curves normal 0 to Z can be obtained a number of 0,2711, that is the contribution of learning models of reciprocal teaching in an increase learning achievement  students  which amounted to 27,11%. In the use of reciprocal teaching models teacher should have a lot times and the students are expected for increase their ability in the search of information related on economic subjects.Keyword: reciprocal teaching, independence, learning achievement